A Sincere Disciple: Colin Rae Brown (1821–1897). Issue 1 (March 2022) - Beck, Alan D.
Abstract : 2021 sees the bicentenary of the birth of Colin Rae Brown, perhaps the most important figure in the development of the Burns movement during the nineteenth century. This article seeks to provide a brief, and long-overdue biographical sketch of this under-researched Burnsian, while simultaneously contextualising Brown's desire to memorialise not only Burns, but also other Scottish icons such as William Wallace, Walter Scott and Highland Mary. It also outlines the connection between Greenock Burns Club's monument to Highland Mary and Brown's contribution to the memorialisation of Burns in general in the second half of the nineteenth century. It is a tribute to the man who, in 1892, founded the present periodical.